(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Aim: The study aimed to assess drug compliance among diabetic patients residing in the rural areas of Dharmapuri district, Tamil Nadu, and to evaluate related factors affecting their quality of life. Methods: A cross-sectional study was conducted from August 2024 to January 2025, involving 100 diabetic patients diagnosed with Type II Diabetes Mellitus. Participants were chosen through quota sampling from two rural areas, with data collected via a structured questionnaire focusing on drug compliance and quality of life across four domains: social health, physical health, physiological health, and environmental health. Results: Gender distribution analysis showed a slightly higher prevalence of diabetes in females (51%) compared to males (49%). Compliance issues were often linked to factors such as knowledge deficits and accessibility to healthcare facilities. Conclusion: Improving patient education and establishing more accessible healthcare services are essential to enhance drug compliance and overall quality of life for diabetic patients in rural areas. These findings underscore the need for targeted interventions to address the unique challenges faced by this population.